THE DIFFERENCES OF GRAMMAR TEACHING METHOD USED BASED ON THE TEACHERS’ LENGTH OF TEACHING EXPERIENCES - Faradila, Nandatul; Yunita, Wisma; Syahrial, Syahrial (Universitas PGRI Sumatera Barat, 2022)
The preference in implementing the suitable method in teaching English grammar is important to be considered in order to achieve the learning aims effectively. This study attempted to investigate the differences of grammar teaching method used by the English teachers based on the length of teachers’ teaching experiences. The explanatory mixed methods design was carried out in this study. Eighty English teachers at the junior high schools in North Bengkulu regency were the participants of the study. The quantitative data were collected through distributing the questionnaire to 80 English teachers. Meanwhile the qualitative data were collected through interviewing eight teachers and observing the classroom teaching practice of three teachers. The results showed that based on the length of teachers’ teaching experiences, the frequently grammar teaching method used similarly was Task-Based Language Teaching (TBLT). The differences were found in the kind of the tasks given and in the implementation of the TBLT in teaching and learning process. This study gives insights for the English teachers to reflect on their grammar teaching in the classroom.